The role of distributional factors in learning and generalising affixal plural inflection: An artificial language study. Issue 9 (21st October 2018) - Nevat, Michael; Ullman, Michael T.; Eviatar, Zohar; Bitan, Tali
ABSTRACT: Inflectional morphology has been intensively studied as a model of language productivity. However, little is known about how properties of the input affect the emergence of productive affixation. We examined effects of three factors on the learning and generalisation of plural suffixation by adults in an artificial language: affix type frequency (the number of words receiving an affix), affix predictability (based on phonological cues in the stem), and diversity (the number of distinct phonological cues predicting an affix). Higher type frequency and predictability facilitated the acquisition of trained inflections. Type frequency contributed to participants' inflections of untrained words early during learning, while reliance on diversity emerged gradually, alongside knowledge of phonological cues. Diversity as well as type frequency contributed to the emergence of default-like inflections, including minority defaults. The results elucidate the role of affix diversity and its interaction with other factors in the emergence of productive linguistic processes.